Enterobacter cloacae endocarditis in a patient with pre-existing valvular heart diseaseand periodontal disease - Cortez-Sandoval, Maicol (2024)
Infective endocarditis remains a potentially lethal disease with varied presentations. Enterobacter cloacae endocarditis has high mortality, partly due to antimicrobial resistance and limited clinical experience. We report a 57-year-old male with chronic heart failure and double aortic lesion, admitted with acute heart failure. Blood cultures were positive for E. cloacae. Despite antibiotics, fever spikes recurred, correlating with dental defocalization evaluations. Echocardiography revealed mitral valve vegetation. Dental necrosis and periodontitis were diagnosed. The patient received a 6-week antibiotic regimen and underwent dental treatment and Bentall surgery. After 3 years, clinical evolution was favorable. The case underscores the complexity of managing E. cloacae endocarditis, emphasizing the importance of timely antibiotics and surgical intervention.